Prioritizing agricultural research for development : (CAB International, 2009)
Systematic empirical analysis is needed to help guide limited public resources to those research areas that have the greatest potential to produce benefits for the poor and the environment. Focusing on priority setting practices utilised in different international agricultural research institutes, this book discusses real world experiences and innovations with priority assessment methods. Chapters present approaches that have been used to articulate, explore and assess impact pathways and research priorities, while also considering their strengths and weaknesses and drawing together methodological lessons.